Antibacterial mechanisms of various copper species incorporated in polymeric nanofibers against bacteria. (December 2020) - Phan, Duy-Nam; Dorjjugder, Nasanjargal; Saito, Yusuke; Khan, Muhammad Qamar; Ullah, Azeem; Bie, Xinyu; Taguchi, Goro; Kim, Ick-Soo
Highlights: Four various copper species incorporated in polyacrylonitrile nanofibers. Antibacterial properties related to release of soluble copper. Shapes of nano copper and copper contents contributing to antibacterial effects. Abstract: The fabrication of as-spun copper (II) sulfate polyacrylonitrile (PAN) composite nanofibers, copper hydroxide nanowires (Cu(OH)2 NWs), copper oxide nanowires (CuO NWs), and copper nanoparticles (Cu NPs) incorporated in/on PAN nanofibers were presented. SEM, TEM, FTIR, XRD, and XPS confirmed the success of the syntheses. The surface wettability was also investigated for all samples. All copper composite nanofibers exhibited considerable antibacterial properties against Escherichia coli ( E. coli ) and Bacillus subtilis ( B. subtilis ) and were compared to each other to investigate the mechanistic actions of different copper species. The results of the antibacterial assays suggested that the antibacterial effects of copper-containing samples were dependent on the release of soluble copper, including copper ions (Cu 2+ ), the shape of the nano copper, and the copper content of the composite nanofibers.